To assist computer exports, House bill seeks to bypass broader 'dual use' measure. - McCutcheon, Chuck (CQ Weekly, 2000)
Despite efforts by some legislators to retain the proposal as part of a wider export-control bill, the fate of which remains in doubt, a measure to accelerate change in the rules for exporting high-performance computers is gaining momentum. On April 13, 2000, the House International Relations Committee approved a bill (HR 3680) to cut from 180 days to 30 days the time that Congress would have to review administration changes to the computer performance levels that would need an export license. Computer industry officials contend that the 180-day waiting period has become overly restrictive in the face of the rapid pace of technological change and the competitive international computer market. A Senate measure to reauthorize the Export Administration Act contains provisions that would cut the computer export review period to 60 days.